A gestão escolar democrática em interlocução com a qualidade na educação infantil - Flôres, Vanessa Medianeira da Silva (2014)
In recent decades, childhood education is constituted as a field of knowledge in construction. And studies, scientific research and public policy has emphasized the importance of this stage of education. This research is justified by being a study in the context of educational practices in childhood education and interaction with public policies, we propose reflections about on democratic school management. The objective was to underland the principles and mechanisms of democratic school management in the daily routine of municipal institutions Childhood Education Santa Maria / RS, and, as reference, the current public policies and the impact on the quality of childhood education. The theoretical framework is based on Ariès (1986), Bujes (2001), Kuhlmann Jr (1998) on the history of childhood and of the institutions that attend young children and Oliveira-Formosinho and Formosinho (2013), about the pedagogy of participation and as in the studies by Campos and others (2006), Moss (2002) and Corrêa (2003) regarding the National Policy on Childhood Education (PNEI) (2006) and the quality of early childhood education. Still in production of Lück (2006), Ferreira (2001), Libâneo (2006) and the statutory bases on the democratic school management. The methodological approach is qualitative by nature epistemological option due to the nature of the study. To collect and production the data we used questionnaires to principals and teachers of municipal institutions of child education surveyed. With this study we showed that the principles and mechanisms of democratic school management, as well as the Municipal Law 4740/03 need to be deepened in the institutions surveyed. Conceive of democratic school management permeates the everyday of the institution of early childhood education and thus has dialogues with the quality of care children that link educational intentions and reverberate in pedagogical practices.